The first meta-analysis of the G96S single nucleotide polymorphism (SNP) of the prion protein gene (PRNP) with chronic wasting disease in white-tailed deer - Won, Sae-Young; Kim, Yong-Chan (Frontiers in Veterinary Science, 2024)
BackgroundPrion diseases are irreversible infectious neurodegenerative diseases caused by a contagious form of prion protein (PrPSc). Since chronic wasting disease (CWD)-infected white-tailed deer are strong carriers of the prion seed through corpses via scavenger animals, preemptive control based on genetic information for a culling system is necessary. However, the risk of CWD-related genetic variants has not been fully evaluated. In the present study, we carried out a quantitative estimation of the risk of a G96S single nucleotide polymorphism (SNP) of the PRNP gene to CWD infection in white-tailed deer.MethodsWe carried out a literature search for genetic data of the G96S (c.286G>A) SNP of the PRNP gene from CWD-infected white-tailed deer and matched controls. We performed a meta-analysis using incorporated eligible studies to evaluate the association of the G96S SNP of the PRNP gene with susceptibility to CWD in white-tailed deer.ResultsWe identified a strong association between the G96S (c.286G>A) SNP of the PRNP gene and susceptibility to CWD infection in white-tailed deer using meta-analysis. We observed the most significant association in the recessive model (odds ratio = 3.0050, 95% confidence interval: 2.0593; 4.3851, p < 0.0001), followed by the additive model (odds ratio = 2.7222, 95% confidence interval: 1.9028; 3.8945, p < 0.0001) and the heterozygote (AA vs. AG) comparison (odds ratio = 2.7405, 95% confidence interval: 1.9215; 3.9085, p < 0.0001).ConclusionTo the best of our knowledge, this was the first meta-analysis of the association between the G96S (c.286G>A) SNP of the PRNP gene and susceptibility to CWD infection.